2002
DOI: 10.1212/wnl.58.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Practice parameter: Initiation of treatment for Parkinson’s disease: An evidence-based review [RETIRED]

Abstract: Abstract-In 1993, the last AAN Practice Parameter on medical treatment of Parkinson's disease (PD) concluded that levodopa was the most effective drug for management of this disorder. Since then, a number of new compounds including non-ergot dopamine agonists (DA) and sustained-release levodopa have been released and studied. Thus, the issue of treatment in de novo PD patients warrants reexamination. Specific questions include: 1) does selegiline offer neuroprotection; 2) what is the best agent with which to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
189
0
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(199 citation statements)
references
References 30 publications
3
189
0
7
Order By: Relevance
“…A total of 27 studies met our inclusion criteria for this review. In order to evaluate the studies on their methodological quality, we applied criteria that have been used in pharmacological treatment trials (Miyasaki, Martin, Suchowersky, Weiner, & Lang, 2002). These criteria classify intervention studies into three categories, broadly defined as:…”
Section: Methodsmentioning
confidence: 99%
“…A total of 27 studies met our inclusion criteria for this review. In order to evaluate the studies on their methodological quality, we applied criteria that have been used in pharmacological treatment trials (Miyasaki, Martin, Suchowersky, Weiner, & Lang, 2002). These criteria classify intervention studies into three categories, broadly defined as:…”
Section: Methodsmentioning
confidence: 99%
“…Since then, LD is once again recommended as a therapeutic intervention to be used early in the course of the disease (Obeso and Schapira, 2009;Schapira, 2009a, c;Schapira et al, 2009;Sethi, 2010), a recommendation that is supported by the American Academy of Neurology Practice Guidelines (Miyasaki et al, 2002). Currently, LD, oral dopamine receptor agonists, and MAO B inhibitors are approved by the Federal Drug Administration (FDA) for use in early and advanced PD, while COMT inhibitors and the broad-spectrum injectable dopamine agonist, apomorphine, are approved only for fluctuating PD symptoms.…”
Section: Dopamine Replacement Therapymentioning
confidence: 99%
“…Practice guidelines from the American Academy of Neurology indicate that the evidence supports many options. 24,134 Several key adverse events received significant attention in recent years and can be summarized in the following manner: melanoma (along with other skin cancers) may occur at an increased rate in PD, but there is no evidence to connect it causally with LD. Modest elevations of homocysteine have been seen with LD, but the importance has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…A practice guideline published by the American Academy of Neurology has indicated that using LD as first-line therapy is an acceptable approach. 24 …”
Section: Dopamine Precursor Therapy: Levodopamentioning
confidence: 99%